ATOMS: ALMA three-millimeter observations of massive star-forming regions – VII. A catalogue of SiO clumps from ACA observations. Issue 3 (14th January 2022) - Liu, Rong; Liu, Tie; Chen, Gang; Liu, Hong-Li; Wang, Ke; Li, Jin-Zeng; Lee, Chang Won; Liu, Xunchuan; Juvela, Mika; Garay, Guido; Dewangan, Lokesh; Soam, Archana; et al.
ABSTRACT: To understand the nature of SiO emission, we conducted ACA observations of the SiO (2-1) lines toward 146 massive star-forming regions, as part of the ALMA Three-millimeter Observations of Massive Star-forming regions (ATOMS) survey. We detected SiO emission in 128 (87.7 per cent ) sources and identified 171 SiO clumps, 105 of which are spatially separated from 3 mm continuum emission. A large amount of the SiO line profiles (60 per cent ) are non-Gaussian. The velocity dispersion of the SiO lines ranges from 0.3 to 5.43 km s −1 . In 63 sources the SiO clumps are associated with H ii regions characterized by H40α emission. We find that 68 per cent (116) of the SiO clumps are associated with strong outflows. The median velocity dispersion of the SiO line for outflow sources and non-outflow sources is 1.91 km s −1 and 0.99 km s −1, respectively. These results indicate that outflow activities could be connected to strongly shocked gas. The velocity dispersion and [SiO]/[H 13 CO + ] intensity ratio do not show any correlation with the dust temperature and particle number density of clumps. We find a positive correlation between the SiO line luminosity and the bolometric luminosity, implying stronger shock activities are associated with more luminous protoclusters. The SiO clumps in associations with H ii regions were found to show a steeper feature in L_sio /L_bol . The SiO line luminosity and the fraction of shocked gas have no apparent evidence of correlation with the evolutionary stages traced by luminosity to mass ratio (L_bol/M ).